Stinkiest! : 20 smelly animals - Jenkins, Steve, 1952- (Jenkins, Steve, 1952- Extreme animals., 2018)
Describes the odors that some animals have developed to stay safe and thrive in their environments, including the striped skunk, the bombardier beetle, and the honey badger.